SPINDLE CELL NEOPLASM OF VAGINA CASE REPORT - Muhammad Akram Malik; Mubshara Naz; Muhammad Sohail (Journal of University Medical & Dental College, 2014)
ABSTRACT: Vaginal spindle cell neoplasm is a very rare tumour .It consists of mesmchymal & epithelial components. The presence of glandular structures and pattern of immunostaining, help in differentiating tomour from other vaginal neoplasm. It usually presents with slowly enlarging nodule in vagina. Reoccurrence is very rare